Analysis of antenna system modeling with the help of simulation technology of navigation equipments - Rustamov, Asad; Hashimov, Elshan; Muradov, Tural; Hashimov, Ruslan; Azizullayev, Mukhtar (Національний технічний університет "Харківський політехнічний інститут", 2025)
In this paper, a new coplanar waveguide CPW (Coplanar Waveguide) fed circular waveguide for ultra-wideband UWB (Ultra WideBand) applications using High-Frequency Structure Simulator (HFSS) and Computer Simulation Technology (CST) software is presented. A comparison of modeling and simulations of disk monopole antenna is presented. The purpose of the research is to first determine the geometric parameters and material properties of the antenna, and then perform simulations using HFSS and CST programs. The task of the research is to evaluate the performance by modeling a new coplanar waveguide-fed circular disk monopole antenna for ultra-wideband applications and to compare the results obtained from these two electromagnetic simulation tools. Modeling of a new coplanar waveguide-fed circular disc monopole antenna for ultra-wideband applications used planar patterns and a coplanar waveguide-fed circular disc monopole antenna providing a wide frequency range. Antenna modeling method was used to solve the problem. High-frequency structure simulator and computer simulation technology have been widely used in microwave studio programs, accuracy in solving electromagnetic problems and antenna modeling. The following results were obtained. High frequency structural simulator and Computer simulation technology has been implemented between 2.3 GHz and 12 GHz. Key parameters such as reflection coefficient (S11), directivity pattern and gain coefficient were analyzed to evaluate the antenna performance.

У цій роботі представлено нову круглу монопольну антену з живленням через співплощинну хвилевідну лінію (CPW – Coplanar Waveguide) для ультраширокосмугових (UWB – Ultra WideBand) застосувань, змодельовану за допомогою програмного забезпечення High-Frequency Structure Simulator (HFSS) та Computer Simulation Technology (CST). Подано порівняльний аналіз моделювання та симуляцій дискової монопольної антени. Метою дослідження є спочатку визначити геометричні параметри та матеріальні властивості антени, а потім провести симуляції за допомогою програм HFSS та CST. Завдання дослідження полягає в оцінці ефективності нової дискової монопольної антени з живленням через CPW для ультраширокосмугових застосувань і порівнянні результатів, отриманих за допомогою двох інструментів електромагнітного моделювання. Результати дослідження. Для моделювання було використано плоскі структури та дискову монопольну антену з CPW-живленням, що забезпечує широкий діапазон частот. Метод моделювання антени було використано для вирішення проблеми. HFSS і CST широко використовуються в програмах моделювання мікрохвильових пристроїв завдяки високій точності при вирішенні задач електромагнітного моделювання та моделювання антен. Було отримано такі результати: HFSS та CST були реалізовані в діапазоні частот від 2.3 ГГц до 12 ГГц. Було проаналізовано ключові параметри, такі як коефіцієнт відбиття, діаграма спрямованості та коефіцієнт підсилення для оцінки продуктивності антени.
Аналіз моделювання антенної системи за допомогою технології симуляції навігаційного обладнання
Keywords: monopole antenna; CPW-fed; circular disc monopole antenna; CST MWS; HFSS; монопольна антена; CPW-живлення; дискова монопольна антена